ROLE OF TYLOPHORA INDICA IN TREATMENT OF BRONCHIAL ASTHAMA: Life Sciences-Botany - UMAMAHESWARI. P1; SAILAJA.V; RAVANAIAH. G; PHANI KUMAR, D.V; C.V.NARASIMHA MURTHY (International Journal of Life Science and Pharma Research, 2022)
Bronchial Asthma is a disease of lungs in which the patient complaining of recurrent attacks of breathlessness and wheezing due to the narrowing of the airways of the lungs. The cause of asthma may be genetic but the disease develops and persists as a result of changes in the environment, food and life style. It is believed that attacks were triggered by allergens. Tylophora indica more simply known as the asthma plant, is nature gift for the long suffering asthmatics. It is called Anantmul in Sanskrit and Verripala in Telugu. The leaves, stem and roots of the plant contain 0.2-0.3% alkaloid called Tylophorine. The emetic properties of the root and leaf were well established. Ayurveda acknowledges “Vamana” as useful in ejecting the afflicted Kapha (Phlegm). The method of “Vamana” is very popular in ayurveda treatment of asthma. Tylophora is very effective in drawing out the scum of kapha from the bronchial tubes resulting in the oxygenation of blood and relieving symptoms of asthma and providing solace to the patient. The mode of treatment, diet regimen was discussed.